(untitled) (Marketing Journal, 2026)
Abstract This article examines methods for improving the implementation of the customeroriented principle in retail marketing activities. A comparative analysis of widely used international instruments, including CRM systems, Net Promoter Score methodology, omnichannel integration, personalized marketing, and customer experience management, is conducted. The current state of Uzbekistanʼs retail market is assessed, taking into account digital infrastructure development and the level of customer-focused technology adoption. Based on the findings, a phased methodological model for implementing a customer-oriented approach is proposed. The recommended framework aims to enhance enterprise competitiveness and strengthen customer loyalty in an increasingly competitive retail environment. Keywords: retail trade, customer orientation, CRM, Net Promoter Score, customer experience, personalization, Uzbekistan.